2009
DOI: 10.4000/discours.7594
|View full text |Cite
|
Sign up to set email alerts
|

Attention and syntax in sentence production: A critical review

Abstract: Abstract:People often speak about visually perceived events that unfold in real time. In doing so speakers regularly translate the details of the visual world they describe onto the grammatical properties of the sentences about it. For example, the speaker needs to map her constantly changing attentional state onto the syntactic plan of the produced sentences. The present paper briefly discusses what attention is, explores methods for the co-activation of attentional and syntactic operations during the product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Ferreira 1994; Prat‐Sala and Branigan 2000; van Nice and Dietrich 2003; Kempen and Harbusch 2004; Rosenbach 2005; Bresnan et al 2007; Dennison 2008) and contextually conditioned properties (accessibility increases with previous mention of the same referent, MacWhinney and Bates 1978; Bock and Irwin 1980; V. S. Ferreira and Yoshita 2003; Prat‐Sala and Branigan 2000; Bresnan et al. 2007; semantic similarity to recently mentioned words, Bock 1986b; Igoa 1996; visual salience , Gleitman et al 2007; Myachykov 2007; Myachykov, Garrod, and Scheepers, forthcoming; Myachykov, Posner, and Tomlin 2007). Production researchers have been interested in conceptual accessibility, because it affects speakers’ word order choices, for example, in active vs. passive voice ( Lightning struck the church vs.…”
Section: Current Findings In Cross‐linguistic Research On Sentence mentioning
confidence: 99%
“…Ferreira 1994; Prat‐Sala and Branigan 2000; van Nice and Dietrich 2003; Kempen and Harbusch 2004; Rosenbach 2005; Bresnan et al 2007; Dennison 2008) and contextually conditioned properties (accessibility increases with previous mention of the same referent, MacWhinney and Bates 1978; Bock and Irwin 1980; V. S. Ferreira and Yoshita 2003; Prat‐Sala and Branigan 2000; Bresnan et al. 2007; semantic similarity to recently mentioned words, Bock 1986b; Igoa 1996; visual salience , Gleitman et al 2007; Myachykov 2007; Myachykov, Garrod, and Scheepers, forthcoming; Myachykov, Posner, and Tomlin 2007). Production researchers have been interested in conceptual accessibility, because it affects speakers’ word order choices, for example, in active vs. passive voice ( Lightning struck the church vs.…”
Section: Current Findings In Cross‐linguistic Research On Sentence mentioning
confidence: 99%
“…One long-standing, attractive hypothesis in the field is that differences in phrasal syntax across languages may support different patterns of incremental planning by requiring speakers to encode some types of information before others. Cross-linguistic studies therefore provide unique insight into possible effects of linguistic structure on early sentence formulation and can help to identify limits in the flexibility of production processes (Brown-Schmidt & Konopka, 2008;Christianson & Ferreira, 2005;Myachykov, Garrod, & Scheepers, 2009;Norcliffe, Konopka, Brown, & Levinson, 2013;Sauppe, Norcliffe, Konopka, van Valin, & Levinson, 2013). …”
Section: Relationship Between Message-level and Sentence-level Structmentioning
confidence: 99%
“…Closer examination of these findings revealed that syntactic network measures were mostly associated with the domains of executive functioning, attention, and information processing speed. These results corroborate emerging literature showing a relationship between syntax and executive functioning (White, Alexander, and Greenfield 2017), attention (Myachykov, Garrod, and Scheepers 2009), and information processing speed (Fernald, Perfors, and Marchman 2006). In SSD, syntactic anomalies might occur at any phase of the grammatical encoding process due to processing speed impairment (Knowles, David, and Reichenberg 2010), reduced inhibitory attentional control (Galaverna, Morra, and Bueno 2012), and/or planning impairments (Holt et al 2013).…”
Section: Association With Cognitionsupporting
confidence: 89%